Evaluasi Proses Bisnis Produksi Area 3 (SRIKANDI) Pada PT Tirta Investama (AQUA) Pandaan Menggunakan Metode Value Chain Analysis, Quality Evaluation Framework (QEF) dan 5 Why's Analysis - Kelvin Yabes Sitompul; Yusi Tyroni Mursityo; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
PT Tirta Investama (AQUA) Pandaan is a company engaged in the production of Bottled Drinking Water. PT Tirta Investama (AQUA) Pandaan produces a variety of products, ranging from 220 ML, 600 ML, 1500 ML, 5 Gallon and Mizone packages. Manufacturing Area 3 (SRIKANDI) is one of the manufacturing divisions at PT Tirta Investama (AQUA) Pandaan that produces 220 ML bottled water. In carrying out the 220 ML packaging production process, there are problems that occur which cause the results of the business process to be carried out not in accordance with the expected targets and can affect the production business process in manufacturing area 3 (SRIKANDI). Based on these problems, it is necessary to conduct an evaluation of the current business processes by identifying current business processes using the Value Chain Analysis method to map the main activities and supporting activities, then determine the quality factors that exist and perform calculations at all quality factors by using the Quality Evaluation Framework (QEF). Then look for the root problem in quality factors that are not in accordance with method 5 Why Analysis. The evaluation results obtained obtained 4 quality factors that were not appropriate, namely in Q5, Q8, Q11 and Q12. The results of these quality factors become problems that can affect the production business processes that are applied.